2021
DOI: 10.1021/acsomega.1c03620
|View full text |Cite
|
Sign up to set email alerts
|

Gemini Lipopeptide Bearing an Ultrashort Peptide for Enhanced Transfection Efficiency and Cancer-Cell-Specific Cytotoxicity

Abstract: Cationic gemini lipopeptides are a relatively new class of amphiphilic compounds to be used for gene delivery. Through the possibility of incorporating short peptides with cell-penetrating functionalities, these lipopeptides may be advantageous over traditional cationic lipids. Herein, we report the design, synthesis, and application of a novel cationic gemini lipopeptide for gene delivery. An ultrashort peptide, containing four amino acids, arginine–cysteine–cysteine–arginine, serves as a cationic head group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Gene transfection potentials of catalogue relating novel cationic lipids are typically assessed either by without serum or with merely 10% (v/v) serum, as described in several previous studies. , Unfortunately, serum incompatibility is still one of the primary roadblocks to cationic transfection lipid clinical effectiveness . The adhesion to positively charged cationic liposome sites by negatively charged serum proteins is thought to be the cause of cationic transfection lipid’s normal serum incompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…Gene transfection potentials of catalogue relating novel cationic lipids are typically assessed either by without serum or with merely 10% (v/v) serum, as described in several previous studies. , Unfortunately, serum incompatibility is still one of the primary roadblocks to cationic transfection lipid clinical effectiveness . The adhesion to positively charged cationic liposome sites by negatively charged serum proteins is thought to be the cause of cationic transfection lipid’s normal serum incompatibility.…”
Section: Resultsmentioning
confidence: 99%
“…Natural amino acid-based cationic lipids could carry and transfect the therapeutic nucleic acid to the various cancerous cells. 19,42 The current lipids tested for transfer of the anti-cancer gene, p53, into the glioma and oral cancer cells led to cell death. When these cells were treated with lipid/p53 lipoplexes, cell viability was dramatically less compared to lipid/pCMV-b-gal lipoplexes at a 2 : 1 N/P ratio (Fig.…”
Section: Cytotoxicity Studymentioning
confidence: 99%
“…22,23 In recent times, the efficiency of αtocopherol as a delivery system in vivo for the delivery of nucleic acids has been reported. 15,24 It is reported from previous studies that α-tocopherol performed similarly as cholesterol in changing liposomes, i.e., making the liposomes highly protein-induced disruption-resistant, and it as found that this inhibition of protein-induced disruption is more effective with tocopherol compared to cholesterol. Therefore, this made tocopherol-based liposomes more efficient vectors for in vivo gene delivery.…”
Section: ■ Introductionmentioning
confidence: 97%
“…Moreover, because of their solvent capacity and biocompatibility, vitamin E-based nanomedicines in cancer therapy have been developed. Furthermore, the serum stability and low toxicity of vitamin E, and the presence of physiological pathways of tocopherol transport to various tissues including brain from blood have led to several investigations on systemic delivery applications. , In recent times, the efficiency of α-tocopherol as a delivery system in vivo for the delivery of nucleic acids has been reported. , It is reported from previous studies that α-tocopherol performed similarly as cholesterol in changing liposomes, i.e., making the liposomes highly protein-induced disruption-resistant, and it as found that this inhibition of protein-induced disruption is more effective with tocopherol compared to cholesterol. Therefore, this made tocopherol-based liposomes more efficient vectors for in vivo gene delivery. ,, Together, impressed by DC-Chol applications and the biological importance of tocopherol, we were inspired to design, synthesize, and evaluate four tocopherol-based cationic derivatives, with varying degrees of methylation, AC-Toc (3β-[ N -(aminoethane)­carbamoyl]­tocopherol) hydrochloride), MC-Toc (3β-[ N -( N ′-methylaminoethane)­carbamoyl]­tocopherol hydrochloride), DC-Toc (3β-[ N -( N ′, N ′-dimethylaminoethane)­carbamoyl]­tocopherol hydrochloride), and TC-Toc (3β-[ N -( N ′, N ′, N ′-trimethylaminoethane)­carbamoyl]­tocopherol hydrochloride).…”
Section: Introductionmentioning
confidence: 99%